Fortunellin-Induced Modulation of Phosphatase and Tensin Homolog by MicroRNA-374a Decreases Inflammation and Maintains Intestinal Barrier Function in Colitis - Xiong, Yongjian; Qiu, Juanjuan; Li, Changyi; Qiu, Yang; Guo, Li; Liu, Yuejian; Wan, Jiajia; Li, Yuchun; Wu, Guokai; Wang, Liang; Zhou, Zijuan; Dong, Jianyi; et al. (Frontiers in Immunology, 2018)
Activation of phosphatase and tensin homolog (PTEN) is known to induce cell apoptosis. MicroRNA-374a (miR-374a), which can suppress PTEN expression, has been found abnormally expressed in inflammatory bowel disease (IBD). Fortunellin is a citrus flavonoid that is a potential anti-inflammation agent in inflammatory diseases. The present study investigated the effects and mechanisms underlying fortunellin-induced inhibition of PTEN in IBD. Colitis was established in rats by the intracolonic administration of 2,4,6-trinitrobenzene sulfonic acid (TNBS) to mimic human ulcerative colitis, which is the main type of IBD. miR-374a expression was measured by quantitative real-time polymerase chain reaction, and the regulation of PTEN by miR-374a was evaluated by dual luciferase reporter assay. Western blotting was used to measure the corresponding protein expression. Fortunellin ameliorated colitis symptoms, including excessive inflammation and oxidative stress. Fortunellin decreased epithelial cell apoptosis through inhibiting PTEN expression in colitis. Fortunellin-induced downregulation of PTEN could be counteracted by miR-374a depletion. Moreover, knockdown of miR-374a in vivo partly inhibited the effects of fortunellin on rat colitis. In conclusion, PTEN inhibition contributes to the amelioration effects of fortunellin on colitis. It was confirmed that fortunellin targets miR-374a which is a negative regulator of PTEN. This study provides novel insights into the pathological mechanisms and treatment alternatives of colitis.